Chirurgische Exzision von Lidtumoren und anschließende ophthalmoplastische Rekonstruktionen. Englische Version - Gaca, P J; Rejdak, R; Lewandowicz, M; Kopecky, A; Kakkassery, V; Heindl, L M (Die Ophthalmologie, 2024)
In recent years new modern therapeutic concepts have been developed in the treatment of malignant eyelid tumors; however, surgical restoration remains an important component of the therapeutic options addressed, which include microsurgical tumor excision into healthy tissue and subsequent coverage of the defects. An ophthalmic surgeon experienced in oculoplastic surgery is responsible for the recognition and evaluation of the existing alterations and planning a procedure together with the patient that meets the patient's expectations. The planning of surgery must always be individualized and fit the initial findings. Depending on the defect size and localization, different coverage strategies are available to the surgeon. To ensure successful reconstruction, every surgeon should master a wide range of reconstructive techniques.
Keywords: Eyelid Neoplasms; chirurgové; nádory očního víčka; Humans; Ophthalmology; zákroky plastické chirurgie; nádory kůže; Surgeons; Plastic Surgery Procedures; Skin Neoplasms; lidé; oftalmologie